Influence of wind speed and road grade on the estimation of drag area in cycling - Polanco, A.; Roa, S.; Suárez, D. R.; López, O.; Muñoz, L. (Sports Biomechanics, 2024)
The estimation of aerodynamic drag in cycling through road tests has the advantage of considering actual cycling conditions. The main drawback is that its accuracy depends on factors of the testing scenario as the wind speed and the road grade. For that reason, the effect of wind speed and road grade on the estimation of drag area ( C D A ) was studied. Numerical and experimental approaches were combined. The numerical approach investigated the sensitivity of C D A to wind speed and road grade perturbations. The experimental approach analysed the effect of including or not wind speed and road grade on the identification of C D A by comparing the changes in the prediction of power delivered. It was found that disregarding small values of wind speed (e.g. 0.5 m/s) and road grade (e.g. gradient of 0.05%) leads to errors in the estimation of C D A of around 10%, referred to the actual value. It was also obtained that the average error of the power prediction when considering wind speed and road grade for the identification of the parameters is about 4.4% and about 25.5% when wind speed and road grade are neglected. It is concluded that including wind speed and road grade data reduces the error on the identification of C D A through outdoor road experiments.